2016
DOI: 10.1016/j.socscimed.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Gender differentials and old age survival in the Nairobi slums, Kenya

Abstract: This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…A possible sex difference in vulnerability to COVID-19 needs to be given keen attention. An ongoing survey in urban slums of Kenya suggested that gender differences need to be looked into with regards to COVID-19 ( 16 ). A recent study confirmed the possible gender difference in curbing epidemics in informal settlements ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A possible sex difference in vulnerability to COVID-19 needs to be given keen attention. An ongoing survey in urban slums of Kenya suggested that gender differences need to be looked into with regards to COVID-19 ( 16 ). A recent study confirmed the possible gender difference in curbing epidemics in informal settlements ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature shows that men tend to have more complex situations due to their having a combination of disabilities that are more likely to generate activity restrictions [31]. To date, little is known about gender differences in disability in Africa, although recent studies have explored this issue and delivered mixed figures, depending on the context [3234].…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from data and observations during the Ebola outbreak in Liberia, cases living in slum communities were expected to have greater numbers of contacts, higher transmission rates due to nature of contacts amidst overcrowding, and to seek care after longer delays than those in less socioeconomically vulnerable settings (Distributions in Supplementary Material Tables 1-2). [30] In addition, based on gender-specific trends in aging, out-migration, and mortality in urban slum communities, [24] differential detection and proportions of symptomatic cases with severe disease were assumed between the subpopulations, as described below. Slum communities in Liberia are also characterized by a strong network of informal leaders who held roles in supervising active case finding efforts, conducted by peernominated community members and in coordination with national surveillance efforts, during the Ebola outbreak.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, selective mortality among slumdwelling adults, combined with trends in out-migration among older adults, has been associated with a higher proportion of females in the 50+ slum-dwelling population in sub-Saharan Africa (SSA). [24] Given the age-dependent gender ratio for severe COVID-19 disease [25,26] --the disease state which most often triggers care-seeking [27] and, in turn, response activities --the concentration of the population in younger age groups and higher proportion female among old age groups could lead to significant undetected, and therefore unsupported, asymptomatic or mildly symptomatic disease in slum communities. This could be further compounded by the higher overall disease burden in slum communities, as mild disease may not be recognized as COVID-19 or perceived as an issue warranting action.…”
Section: Introductionmentioning
confidence: 99%